2020
DOI: 10.1111/1365-2656.13268
|View full text |Cite
|
Sign up to set email alerts
|

Does social thermal regulation constrain individual thermal tolerance in an ant species?

Abstract: In ants, social thermal regulation is the collective maintenance of a nest temperature that is optimal for individual colony members. In the thermophilic ant Aphaenogaster iberica, two key behaviours regulate nest temperature: seasonal nest relocation and variable nest depth. Outside the nest, foragers must adapt their activity to avoid temperatures that exceed their thermal limits. It has been suggested that social thermal regulation constrains physiological and morphological thermal adaptations at the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 81 publications
3
17
0
Order By: Relevance
“…Here, we focus on foraging niche breadth of adult workers rather than the nest sites of colonies. The persistence of a colony at a site will be contingent on both nest success and foraging success but nests can be buffered from external temperature variation, through either nest construction (Jones & Oldroyd, 2006) or social thermal regulation (Villalta et al., 2020), whereas foragers must cope with thermal extremes (Jayatilaka et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on foraging niche breadth of adult workers rather than the nest sites of colonies. The persistence of a colony at a site will be contingent on both nest success and foraging success but nests can be buffered from external temperature variation, through either nest construction (Jones & Oldroyd, 2006) or social thermal regulation (Villalta et al., 2020), whereas foragers must cope with thermal extremes (Jayatilaka et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ants adapt their thermal tolerance to local conditions (Villalta et al 2020). It is well established that E. ruidum is a thermophilous species on the local scale (Schatz & Lachaud 2008;Santamaría et al 2009), which could explain the high densities of this species found in oil palm plantations that consist of open and sunny areas.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal limits are a major factor in structuring species distributions across broad environmental gradients (Diamond et al, 2012). Ants also adapt their thermal tolerance to local conditions (Bujan & Kaspari, 2017;Diamond, Chick, Perez, Strickler, & Martin, 2017;Villalta et al, 2020); we have known this ever since Mary Talbot invented equipment and protocols to measure critical thermal maxima (Talbot, 1943). In temperate environments, it appears that the ability to withstand cold may be more predictive of distributions than the ability to withstand heat (Bishop, Robertson, Van Rensburg, & Parr, 2017;Bujan, Roeder, de Beurs, Weiser, & Kaspari, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Because it is energetically expensive to tolerate high heat, ant colonies must experience selective pressures to decrease investment into thermal tolerance for those experiencing cooler temperatures, such as nest-bound workers and foragers that leave the nest in cooler temperatures (Cerdá & Retana, 2000;Gehring & Wehner, 1995;Ribeiro, Camacho, & Navas, 2012;Talbot, 1934;Willot, Gueydan, & Aron, 2017). In a recent experiment, Villalta et al (2020) demonstrated how colonies of Aphaenogaster iberica ants move their nests and modify the structure of nests to respond to seasonal temperature changes, and showed that colonies manage thermal challenges through a combination of colony-level behaviors, adaptive physiological responses, and individual foraging decisions. We know less about how intracolonial variation in thermal tolerance is actively managed by colonies.…”
Section: Introductionmentioning
confidence: 99%